Genes in pediatric pulmonary arterial hypertension and the most promising BMPR2 gene therapy - Dai, Lingling; Du, Lizhong (Frontiers in Genetics, 2022)
Pulmonary arterial hypertension (PAH) is a rare but progressive and lethal vascular disease of diverse etiologies mainly due to proliferation of endothelial cells, smooth muscle cells in pulmonary artery and fibroblasts, and which ultimately leads to right heart hypertrophy and cardiac failure. Recent genetic studies of childhood-onset PAH reports that there is a greater genetic burden in children than that in adults. Since the first-identified pathogenic gene of PAH, BMPR2, which encodes bone morphogenetic protein receptor 2, a receptor in the transforming growth factor-β superfamily, was discovered, novel causal genes have been identified and substantially sharpened our insights of the molecular genetics of childhood-onset PAH. Currently, some new identified deleterious genetic variants in additional genes implicated in childhood-onset PAH, such as potassium channels (KCNK3) and transcription factors (TBX4 and SOX17), have been reported and greatly updated our understanding of the disease’s mechanism. In this Review, we summarized and discussed the advances of genetic variants underlying childhood-onset PAH susceptibility and potential mechanism, and the most promising BMPR2 gene therapy and gene delivery approaches to treat childhood-onset PAH in the future.